Factors influencing the acceptance of electric vehicles in Malaysia: Extended technology acceptance model analysis - Ting Tin Tin; Chua Kar Wai; Khoo Lik Xiang; Chester Ching Yee Kin; Chaw Jun Kit; Wan Nor Al-Ashekin Wan Husin; Ali Aitizaz; Lee Kuok Tiung; Ayodeji Olalekan Salau; Umar Farooq Khattak; Yasin Ahmed Siddiqui (Scopus, 2024)
Understanding the factors that impact the acceptability of electric vehicles (EVs) is becoming important as the global automotive industry moves toward sustainable transportation solutions, particularly in emerging economies like Malaysia. However, obstacles such as high initial costs and limited charging infrastructure impede the widespread adoption of electric vehicles (EVs) in Malaysia. For this reason, we conducted a survey to a sample of Malaysian respondents to examine the acceptance of electric vehicles in Malaysia using Technology Acceptance Model (TAM). We obtained a total of 114 valid respondents through questionnaires, and the results show that each of the hypotheses was supported. Overall, the contribution of a study on the factors influencing the acceptance of electric vehicles in Malaysia lies in its potential to inform policy, drive market development, promote sustainability and facilitate the transition towards a cleaner and more sustainable transportation system.